Biofortificação agronômica de alface com zinco em cultivo hidropônico - Lima, Bianca Machado de (Universidade Federal de São Carlos, 2021)
Lettuce is the most cultivated leafy vegetable in a hydroponic system. The biofortification of lettuce with Zn can contribute to supply nutritional deficiencies of populations in social vulnerability, for having an affordable price and being easy and fast to produce, even in urban areas. The objective was to evaluate the effect of different concentrations of Zn in hydroponic solution, in the production and biofortification of two lettuce cultivars. The experimental design was completely randomized, in a split-plot scheme, with four replications. The plot was formed by the concentrations of zinc 0,3, 1,0, 1,7, and 2,4 g L-1 in the hydroponic solution, added in the form of zinc sulfate (ZnSO4.7H2O) and the subplots by the cultivars of lettuces Vanda and Saladela. The characteristics evaluated were: plant diameter, root length, number of leaves, fresh and dry mass of the aerial part and root, leaf color (Colorimetry) and chlorophyll index, leaf and root zinc content and accumulation. The concentration of Zn influenced the number of leaves and root length, with the concentration of 2,4 g L-1 of Zn providing the largest number of leaves and root length. For colorimetry a * there was an interaction effect, for Saladela and Vanda the concentrations 0,3 and 2,4 g L-1 showed better results, respectively. For fresh mass of the aerial part Vanda presented higher biomass. For the content and accumulation of Zn in the leaf and root, the concentration of 2,4 g L-1 of Zn showed the best result. It was observed that the highest concentration of Zn did not affect most of the productive characteristics of the culture, mainly in mass of aerial part. It was possible to biofortify the lettuces agronomically and there was no phytotoxic effect on the plants.
Biofortification agronomic of lettuce with zinc in hydroponic cultivation
Keywords: Lactuca sativa L; Hortaliça folhosa; Sulfato de zinco; Teor de nutrientes; Leafy vegetable; Zinc sulfate; Nutrient content; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA